COMPARATIVE EFFICIENCY OF DISINFESTATION OF EXCREMENTS OF DIFFERENT KINDS AGRICULTURAL ANIMALS BY CHEMICAL REAGENTS - Довгій, Ю. Ю.; Фещенко, Д. В.; Рябцева, Н. О.; Згозінська, О. А.; Корячков, В. А. (Scientific Progress & Innovations, 2013)
The results of influence of oxide of calcium on efficiency of disinfestation of organic wastes are given. The desinvasion effect of chemical solutions on the exciters of widespread nemathodosis of animals is set. It is set that maximal efficiency of disinfestation of pus arrives at at a temperature 70 – 100°S and thermal effect of 120 – 220 kDzh. A high desinvasion action is certain 1,5 % solution of brovadez-20 under ascarosis of pigs and 2 % krystal-1000, vetoks, brovadez-plus under strongilyatoses of horses. Dezinvazive effect of compounds in relation to the exciters of parasitosis depends on the concentration of workings solutions.